Evaluasi Pelaksanaan Prenatal Yoga Dengan Kualitas Tidur Ibu Hamil Trimester Iii Di Klinik Olive Sahabat Bunda - Putri, Dhea Adiyani; Istiqamah, Istiqamah; Budi, Setia (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
One of the complaints that are often experienced by pregnant women is sleep disorders. Sleep disorders that occur in pregnant women are a reduction in sleep duration. According to a 2012 survey by the National Sleep Foundation, about 78% of pregnant women in America have trouble sleeping. While in Indonesia 97% of pregnant women experience sleep disorders in the third trimester. The purpose of this study is to determine the evaluation of the implementation of prenatal yoga with the quality of sleep of III trimester pregnant women at the Olive Sahabat Bunda Clinic. This research method is a quantitative research type of descriptive analytical research design used is one group pre test post test design. The number of samples used was 30 respondents. The variables of the study were prenatal yoga and sleep quality. The measuring instrument or instrument in this study was the Pittsburg Sleep Quality Index (PSQI) questionnaire. The results of this study showed that before prenatal yoga, 23 respondents (23.3%) had poor sleep quality at night and only 7 respondents (76.7%) had good sleep quality.